PENERAPAN ETIKA PEMASARAN ISLAM DALAM PENGGUNAAN DIGITAL MARKETING PADA USAHA KECIL MENENGAH (UKM) - Yera Ichsana; Hilda Monoarfa; Fitranty Adirestuty (Schemata: Jurnal Pascasarjana UIN Mataram, 2019)
The purpose of this study is to find out and describe in general how the level of application of Islamic marketing ethics in the use of digital marketing in SMEs through a quantitative descriptive approach. The analysis technique used in this study is to look for the average demographic data that has been filled by respondents. The subjects of this study are SMEs who have done marketing using digital marketing operating in the city of Bandung with a total of 30 respondents. Furthermore, the sampling technique that the researchers used was non-probability sampling with convenience types to make it easier for researchers to obtain samples. The results of this study indicate that the average percentage of all dimensions has a very good category. So, it can be said that the application of Islamic marketing ethics in the use of digital marketing in SMEs in Bandung has been very good. Meanwhile, the dimension that has the highest average percentage value is the dimension of being serving and being humble. However, there are still dimensions that have not been categorized as very good, namely the dimensions of behaving well and sympathetic and do not like to bad-mouth.